Faktor Risiko Obesitas Pada Remaja - Pujiati, Pujiati; Podojoyo, Podojoyo; Sihite, Nathasa Weisdania; Abidin, Zainal (Badan Penelitian dan Pengembangan Daerah Provinsi Sumatera Selatan, 2025)
An unbalanced lifestyle and diet can lead to obesity both in cities and in rural areas. The purpose of this study is to determine the prevalence of obesity and identify risk factors for obesity in adolescents using a survey approach with a case-control design. The sample was 35 obese adolescents and 35 normal adolescents who were selected at random. The results of the prevalence study, conducted in 555 people, showed that 6.48% of the adolescents were obese, 10.09% were overnourished, 72.79% were normal, 6.13% were undernourished, and 4.68% were malnourished. The results of the Chi Square statistical test showed a relationship of energy intake (p-value 0.000) with an OR value of 57.578; carbohydrate intake (p-value 0.007) OR value 8.609); protein intake (p-value 0.003), fat intake (p-value 0.000) OR value 23.273; physical activity (p-value 0.000) OR value 6.769; dietary fiber intake (p-value 0.007) OR value 8.609; nutritional knowledge (p-value 0.000) OR value 10.154 with obesity. Excess energy intake, excess carbohydrates, and excess fat are risk factors for obesity. Lack of physical activity, lack of knowledge, and lack of dietary fiber intake are risk factors for obesity Keywords: Intake, Activity, Energy, Adolescents, Obesity, fibre